Sistem Informasi Geografis Pasar Tradisional Berbasis Web di Wilayah Kabupaten Badung - I Gede G Sastrawan; I Nyoman Yudi Anggara Wijaya (Universitas Harapan Bangsa, 2020)
Abstract— Traditional markets are a place for sellers of basic necessities produced by small and medium scale economic actors. The need for information on traditional markets for the community in Badung Regency is a very important instrument considering the very limited information about traditional markets such as market location information, market commodities and other information that is beneficial to the community. Lack of complete information makes some traditional markets in Badung Regency not yet well known. By utilizing information technology such as web-based geographic information systems, it can provide complete traditional market information to the public who want to know the traditional markets that are in the vicinity. The existence of this geographic-based information system is expected to be one of the solutions for data processing and information on traditional markets in Badung Regency, namely by building a web-based Geographic Information System (GIS) where in the system there are also market information and important information relating to traditional markets in the Badung regency. The software development carried out in this study uses the Waterfall method. This method is also called the Classic Life Cycle method. Called the Waterfall method because the first stage must be passed and finished first to be able to proceed to the next stage.